Stay or return? The role of city environment and digital economy in migrants in China - Chen, Qiang; Qi, Ping; Deng, Lanfang (Frontiers in Environmental Science, 2024)
With the rapid development of digital economy, green environment and digital economy are constantly and deeply integrated. This paper examines the effect of city environment and digital economy on return intention. The results of this study show that both urban environment and digital economy have a significant impact on laborers' decisions about return migration. Moreover, the study reveals that the older individuals are more responsive to the environmental quality, while the decisionmaking process regrading return migration is more evidently influenced by the digital economy for individuals with higher abilities and those within province.Furthermore, the wages of the migrants who intend to return also increase with the growth of the city's digital economy, which may be attributed to the enhanced work efficiency. In addition, the increased impact of the green environment and digital economy on wages for the migrants intending to return is primarily observed in the middle-skilled and middle-income laborers.